2020
DOI: 10.1016/j.ultrasmedbio.2020.03.003
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Reliable Protocol to Objectively Assess Scar Stiffness Using Shear Wave Elastography

Abstract: The aim of this research was to investigate the use of shear wave elastography as a novel tool to quantify and visualize scar stiffness after a burn. Increased scar stiffness is indicative of pathologic scarring which is associated with persistent pain, chronic itch and restricted range of movement. Fifty-five participants with a total of 96 scars and 69 contralateral normal skin sites were evaluated. A unique protocol was developed to enable imaging of the raised and uneven burn scars. Intra-rater and inter-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…83,84 More recently, shear wave elastography has been applied to objectively measuring human scar stiffness, where it reliably measured the stiffness of burn scars in a non-invasive manner. 85 This study further demonstrated that novice ultrasonographers became just as reliable as experienced ultrasonographers following a short training session in, further supporting elastography's possible role in a bedside clinical environment of wound evaluation. Elastography is limited in its use, however, as its spatial resolution is large and is unable to resolve microscopic details necessary for evaluation of collagen microstructures.…”
Section: High Frequency High Resolution Ultrasound Imagingsupporting
confidence: 65%
“…83,84 More recently, shear wave elastography has been applied to objectively measuring human scar stiffness, where it reliably measured the stiffness of burn scars in a non-invasive manner. 85 This study further demonstrated that novice ultrasonographers became just as reliable as experienced ultrasonographers following a short training session in, further supporting elastography's possible role in a bedside clinical environment of wound evaluation. Elastography is limited in its use, however, as its spatial resolution is large and is unable to resolve microscopic details necessary for evaluation of collagen microstructures.…”
Section: High Frequency High Resolution Ultrasound Imagingsupporting
confidence: 65%
“…Moreover, it is documented in the literature that hamstring muscle stiffness results may be influenced by age [ 88 , 89 ], genetics [ 88 , 90 ], sex [ 91 ], sports profession [ 39 , 92 ], pelvic tilt type [ 93 ], hip and knee positions [ 94 ], injury and scar status [ 32 34 ], and operator of the shear-wave elastography [ 95 ]. Besides reasons based on the characteristics and history of the individual, stiffness results of the BFlh vary between different ultrasound brands and versions even at similar measurement positions in healthy participants.…”
Section: Discussionmentioning
confidence: 99%
“…The process was repeated on the contralateral side, then repeated bilaterally with the arm in abduction. Additionally, extra SWE images were acquired of the skin using the same protocol and a previously developed custom 'gelwell' stand-off [21] . The 'gel-well' is a rectangular silicon structure with a central cut-out designed to contain transmission gel so that a standard thickness of 10mm gel is maintained.…”
Section: Procedurementioning
confidence: 99%